2005
DOI: 10.1016/j.febslet.2005.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Auxin‐induced reactive oxygen species production requires the activation of phosphatidylinositol 3‐kinase

Abstract: We recently reported that production of reactive oxygen species (ROS) is essential for auxin-induced gravitropic signaling. Here, we investigated the role of phosphatidylinositol 3-kinase and its product, PtdIns(3)P, in auxin-mediated ROS production and the root gravitropic response. Pretreatment with LY294002, an inhibitor of PtdIns 3-kinase activity, blocked auxin-mediated ROS generation, and reduced the sensitivity of root tissue to gravistimulation. The amount of PtdIns(3)P increased in response to auxin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 37 publications
5
97
1
2
Order By: Relevance
“…To achieve this, pollen tubes undergo highly polarized, tip-localized expansion, which depends on a complex signaling network that includes ion fluxes and gradients, cytoskeletal reorganization, and membrane trafficking (Hepler et al, 2001). Among the components of the signaling network for tip growth, reactive oxygen species, Ca 21 , cytoskeleton, or membrane trafficking have been shown to be affected by PI3K in other plant cell types, including guard cells (Jung et al, 2002;Park et al, 2003;Joo et al, 2005;Leshem et al, 2007;Choi et al, 2008). In particular, it is worth mentioning that a major G-actin-binding protein present in pollen, profilin, was recently shown to bind VPS34/PI3K from bean (Phaseolus vulgaris; Aparicio-Fabre et al, 2006) and that PI3K activity in cultured carrot (Daucus carota) cells associates with the cytoskeleton (Dove et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this, pollen tubes undergo highly polarized, tip-localized expansion, which depends on a complex signaling network that includes ion fluxes and gradients, cytoskeletal reorganization, and membrane trafficking (Hepler et al, 2001). Among the components of the signaling network for tip growth, reactive oxygen species, Ca 21 , cytoskeleton, or membrane trafficking have been shown to be affected by PI3K in other plant cell types, including guard cells (Jung et al, 2002;Park et al, 2003;Joo et al, 2005;Leshem et al, 2007;Choi et al, 2008). In particular, it is worth mentioning that a major G-actin-binding protein present in pollen, profilin, was recently shown to bind VPS34/PI3K from bean (Phaseolus vulgaris; Aparicio-Fabre et al, 2006) and that PI3K activity in cultured carrot (Daucus carota) cells associates with the cytoskeleton (Dove et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…PtdIns(3)P is essential for normal plant growth (Welters et al, 1994) and has been implicated in diverse physiological functions, including root nodule formation (Hong and Verma, 1994), auxin-induced production of reactive oxygen species and root gravitropism (Joo et al, 2005), root hair curling and Rhizobium infection in Medicago truncatula (Peleg-Grossman et al, 2007), increased plasma membrane endocytosis and the intracellular production of reactive oxygen species in salt tolerance response (Leshem et al, 2007), stomatal closing movement (Jung et al, 2002;Park et al, 2003), and root hair elongation . Cellular and biochemical mechanisms of action of PtdIns(3)P are the focus of intense investigation.…”
mentioning
confidence: 99%
“…Many heavy metals, including Pb, are known to induce over production of ROS and consequently enhance lipid peroxidation, decrease the saturated fatty acids and increase the unsaturated fatty acid contents of membranes of several plant species (Halliwell and Gutteridge, 1999;Malecka et al, 2001). IAA also generates ROS, excites oxygen intermediates (De Melo et al, 1992;Joo et al, 2005) and increases MDA content in various rat tissues (Celik and Tuluce, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is synthesized by phosphatidylinositol 3-kinase (PI3K), which in turn is encoded by the only PI3K gene reported in plants, VPS34. PtdIns(3)P and PI3K are essential for normal plant growth (Welters et al, 1994) and have been implicated in diverse physiological functions, including root nodule formation (Hong and Verma, 1994), auxin-induced production of ROS and root gravitropism (Joo et al, 2005), root hair curling and Rhizobium infection in Medicago truncatula (PelegGrossman et al, 2007), increased plasma membrane endocytosis and the intracellular production of ROS in the salt tolerance response (Leshem et al, 2007), and stomatal closing movement (Jung et al, 2002;Park et al, 2003).…”
mentioning
confidence: 99%
“…We hypothesized that PtdIns(3)P is important for tip growth of root hair cells because (1) ROS and the cytoskeleton, essential factors for root hair cell growth, are modulated by PtdIns(3)P in other cell types (Park et al, 2003;Joo et al, 2005;Leshem et al, 2007;Choi et al, 2008) and (2) PtdIns(3)P is essential for normal morphology and movement of endosomes in root hairs (Voigt et al, 2005). Using pharmacological and genetic tools, we found that the maintenance of a normal level of PtdIns(3)P is required for root hair elongation.…”
mentioning
confidence: 99%